The vehicle relocation problem with operation teams in one-way carsharing systems. Issue 12 (18th June 2022) - Lu, Yuwei; Wang, Kangzhou; Yuan, Biao
Abstract : The imbalance of available vehicles at different stations is an outstanding challenge in one-way carsharing systems. Dedicated to this issue, the operation teams in one company in Shanghai, China, each of which contains several workers, take operation vehicles to rebalance sharing vehicles among stations. A pertinent optimization problem, called the vehicle relocation problem with operation teams, is encountered in practice to find the relocation pairs of stations and the visiting routes of operation vehicles. In this paper, a mathematical programming model for minimizing the sum of relocation distance of sharing vehicles and travel distance of operation vehicles is constructed. An adaptive large neighbourhood search algorithm with several problem-specific algorithmic components is developed to efficiently solve the problem. Computational results validate the competitive performance of the proposed approach by comparing it with the commercial optimization software and a sequential approach.